Environmental Ethics: The State of the Question. (Southern Journal of Philosophy, 2021)
Environmental ethics, as an academic field, was born out of professional philosophers' frustrations with anthropocentrism. In particular, philosophers such as Richard Sylvan and Holmes Rolston III found that canonical Western philosophy overlooked important questions regarding human relations to nonhuman animals and the broader world. Because many other traditions attend more closely to these relations, it is helpful to contextualize the initial development of academic environmental ethics as a critical response to a particular kind of deficiency characteristic of the Western tradition. In recent decades, the field has grown and broadened, and a more pluralistic, interdisciplinary, intercultural, and intersectional environmental ethics is emerging. This article traces developments in the field of environmental ethics during the last fifty years, beginning with discussions of the value of nature, deep ecology, the land ethic, environmental virtue ethics, and environmental pragmatism. Next, I turn to approaches that integrate social and environmental concerns through lenses that consider power dynamics and challenge relations of domination and oppression, bringing into focus questions of environmental and ecological justice. The final section considers some of the distinctive challenges associated with what some have dubbed "the Anthropocene," noting that the nature and designation of this epoch remain contested.